Quality of life, anxiety prevalence, depression symptomatology and suicidal ideation among acne patients in Lithuania. (4th August 2017) - Lukaviciute, L.; Navickas, P.; Navickas, A.; Grigaitiene, J.; Ganceviciene, R.; Zouboulis, C.C.
Abstract: Background/Objective: We aimed to determine the prevalence of anxiety, depression symptomatology and suicidal ideation among patients with acne and the impact of this skin condition on the quality of life in Lithuania. Methods: The mental health of patients with acne was assessed using an adapted Hospital Anxiety and Depression Scale, the Dermatology Quality of Life Index, questions about characteristics of acne. The study was authorized by the Regional Biomedical Research Ethics Committee. Results: A total of 255 responders of 324 patients with acne included (84.4%) were assessed. 56.1% of the responders had comorbid anxiety, depression symptomatology or suicidal ideation related to acne. Among them, 38.4% had anxiety symptoms, 23.1% had depression symptoms and 12.9% had suicidal thoughts due to acne. About 96.5% of the responders had a reduced quality of life due to acne. Conclusion: More than a half of the patients with acne who participated at the study had comorbid emotional disorders. Anxiety was the most prevalent sign, 1.7‐fold more prevalent than depression and threefold more prevalent than suicidal ideation. Depression was prevalent in more than every fourth responder and suicidal ideation afflicted every eighth acne patient. More than 90% of the patients had impaired life quality.